STUDY OF RELATIONSHIP BETWEEN UNDERSTANDING ABOUT NATIONAL INSIGHTS WITH ATTITUDE AND NATIONALISM SOULS IN CLASS VIII STUDENTS OF STATE 4 SCHOOLS NEGARA INDONESIA - Abdul Halim; Muhammad Chafidz Ali Wafa (International Jurnal of Education Schoolars, 2020)
Indonesia's nationalism before the independence era was based on the struggle of heroism in seizing independence from the oppression of chauvinistic imperialists. But nationalism in the current era of development is no longer a form of heroism's struggle to win independence from the colonizers, but rather nationalism is expected, so that it can bring the struggle of the Indonesian people to be able to compete globally in technological competition and the world economy which incidentally in western hegemony. The formulation of the problem is is there a relationship between the understanding of Nationality Insights with the attitude and spirit of Nationalism in the eighth grade students of SMP Negeri 4 Negara. The method of determining the research area using the purposive area method. In determining research respondents, researchers used the Proportional Random Sampling Technique method. The data collection methods in this study are as follows: 1) questionnaire and questionnaire methods; 2) interview method; 3) documentary method. While in the method of analyzing data with statistics, the statistical formulation used is the tetrachoric correlation technique. From the results of data analysis and hypothesis testing, it is known that the value of rxy: 0.670, while the magnitude of the relationship is calculated in the table (0.341) for TS. 5% and N = 100. Thus the null hypothesis (Ho proposed is rejected), because r count is greater than r table. So the hypothesis reads, "There is a correlation between Nationality Insights and the attitude and spirit of nationalism in Class VIII students in SMP Negeri 4 Negara".